The role of bariatric and metabolic surgery in the development, diagnosis, and treatment of endometrial cancer - Ross, Robert C.; Akinde, Yetunde M.; Schauer, Philip R.; le Roux, Carel W.; Brennan, Donal; Jernigan, Amelia M.; Bueter, Marco; Albaugh, Vance L. (Frontiers in Surgery, 2022)
The obesity pandemic continues to contribute to a worsening burden of disease worldwide. The link between obesity and diseases such as diabetes, cardiovascular disease, and cancer has been well established, yet most patients living with obesity remain untreated or undertreated. Metabolic and bariatric surgery is the most effective and durable treatment for obesity, is safe, and may have a protective benefit with respect to cancer incidence. In this review, an overview of the link between obesity, metabolic surgery, and cancer is discussed with emphasis on indications for endometrial cancer, the malignancy most strongly associated with obesity. Considerable evidence from retrospective and prospective cohort studies supports a decreased risk of endometrial cancer in patients with obesity who undergo bariatric surgery compared to non-surgical controls. Survivors of endometrial cancer are at increased risk of poor health outcomes associated with obesity, and women with endometrial cancer are more likely to die of cardiovascular disease and other obesity related illness than of the malignancy itself. Recent advances in anti-cancer drug therapies have targeted pathways which may also be therapeutically altered with metabolic surgery. Metabolic surgery has significant potential to enter the treatment paradigm for endometrial cancer, and gynecologic oncologist visits present an opportunity to identify patients who may benefit most.